One‐pot modification of Fe3O4 to prepare Fe3O4/SiO2/C nanoparticles and their catalytic activity in Fenton‐like process for dye decolouration. (1st November 2016) - Xue, Fumin; Yang, Sheng‐Tao; Jin, Xinyan; Li, Tongtong; Wang, Ruijue; Liu, Xiaoyang; Bai, Yitong; Chen, Lingyun; Ming, Zhu; Yang, Hua
Abstract : Heterogeneous catalysis of Fenton‐like process provides new alternatives to overcome the drawbacks of traditional Fe 2+ ‐H2 O2 system. Herein, the modification of Fe3 O4 with SiO2 /C in one‐pot hydrothermal reaction to prepare Fe3 O4 /SiO2 /C nanoparticles (FSCNP) for the Fenton‐like catalysis in neutral environment is reported. FSCNP could catalyse the decomposition of H2 O2 at various pH values to decolourise methylene blue (MB), in particular the neutral pH 7.5. Correspondingly, the chemical oxygen demanding of MB solution was significantly removed. FSCNP‐H2 O2 system was resistant to radical scavengers. Higher H2 O2 concentration and temperature would accelerate the decolouration of MB in FSCNP‐H2 O2 system. The implications to the future applications of FSCNP in dye decolouration and water treatment are discussed.